Intra-unit reliability and movement variability of submission grappling external load as measured by torso mounted accelerometery - Christopher Kirk; James Malone; Peter Angell (Termedia Publishing House, 2022)
Submission grappling consists of skills and movements used in combat sports to physically control opponents whilst trying to apply choke holds and joint locks. There is currently no accepted method of monitoring external load in grappling-based sports due to the absence of key variables such as distance, velocity or time. The primary aim of this study was to determine whether PlayerLoad is a reliable variable for measuring external load of submission grappling movements, with a secondary aim of determining the between repetition variance of submission grappling movements. 7 experienced submission grapplers were recruited. Each wore a torso mounted Catapult® Optimeye S5 microelectromechanical systems (MEMS) device and completed 5 repetitions of each of the following: 4 submission techniques; 5 transition techniques; 2 guard pass techniques; 2 takedown techniques. Accumulated PlayerLoad (PLdACC) was recorded as a marker of absolute load, with accumulated PlayerLoad per minute (PLdACC∙min-1) representing relative load. Reliability of each was assessed using intraclass correlation coefficient (ICC(3,1)) (≥ 0.70). Between repetition movement variation was assessed via coefficient of variation with 95% confidence intervals (CV, 95%CI) (acceptable ≤ 15%, good ≤ 10%). PLdACC ICC(3,1) range = 0.78-0.98, with CV range = 9-22%. PLdACC∙min-1 ICC(3,1) range = 0.83-0.98, with CV range = 11-19%. Though several variables displayed CV > 15%, all had 95%CI lower boundaries ≤ 15%. Whilst PlayerLoad was found to be a reliable measure for submission grappling, relatively high CVs across most techniques examined suggest PlayerLoad may not be appropriate for measuring changes in external load for individual movements in submission grappling. However, it may prove a useful tool for monitoring the external load of full, grappling-based, training sessions within an individual.